2016
DOI: 10.7567/jjap.55.1202bf
|View full text |Cite
|
Sign up to set email alerts
|

Defect characterization of β-Ga2O3 single crystals grown by vertical Bridgman method

Abstract: The characteristics of structural defects observed on (100) wafers in β-Ga2O3 single crystals grown by directional solidification in a vertical Bridgman furnace were studied in terms of crystal growth conditions. No high-dislocation-density regions near the wafer periphery were observed owing to the lack of adhesion between the as-grown crystal ingot surface and the crucible inner wall, and directional solidification growth in a crucible with a very low temperature gradient resulted in β-Ga2O3 single crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 34 publications
1
59
0
2
Order By: Relevance
“…An extensive review of Ga 2 O 3 material properties, processing routes and devices was recently published by Pearton et al, 3 while b-Ga 2 O 3 , in particular, was reviewed by Park et al 4 The material has, indeed, found a wide range of applications in various disciplines. Single-crystals of Ga 2 O 3 were synthesized by low-cost, melt growth techniques 5 and were implemented in power electronic devices with high breakdown voltages, as replacements for the costly SiC and GaN. 6 Thin layers of Ga 2 O 3 have been applied in solar cells, for example as an ultrathin tunneling layer in dye-sensitized solar cells 7 or as a passivation layer on silicon solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review of Ga 2 O 3 material properties, processing routes and devices was recently published by Pearton et al, 3 while b-Ga 2 O 3 , in particular, was reviewed by Park et al 4 The material has, indeed, found a wide range of applications in various disciplines. Single-crystals of Ga 2 O 3 were synthesized by low-cost, melt growth techniques 5 and were implemented in power electronic devices with high breakdown voltages, as replacements for the costly SiC and GaN. 6 Thin layers of Ga 2 O 3 have been applied in solar cells, for example as an ultrathin tunneling layer in dye-sensitized solar cells 7 or as a passivation layer on silicon solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Etching temperature was optimized over the range of 200–490 °C for the purpose of dislocation revelation. In comparison with KOH aqueous solution, molten alkali solution allows chemical etching above 100 °C. Activation energy of chemical reaction was calculated using temperature‐dependent etch rate.…”
Section: Methodsmentioning
confidence: 99%
“…A Baliga low‐frequency figure of merit over 3000 times greater than Si, and several times greater than competitive WBG power semiconductors such as 4H‐SiC and wurtzite GaN, has been predicted . Because of the availability of high‐purity Ga 2 O 3 melt, β‐Ga 2 O 3 can be grown by a variety of melt growth methods, including edge‐defined film‐fed growth (EFG), floating zone (FZ), Czochralski (CZ), and vertical Bridgman (VB) . This gives β‐Ga 2 O 3 a great advantage over 4H‐SiC and GaN in terms of wafer cost and wafer diameter.…”
Section: Introductionmentioning
confidence: 99%
“…с шириной запрещенной E g ≥ 4 эВ. Среди большого разнообразия широкозонных материалов оксид галлия оказывается одним из наиболее перспективных полупроводников для разработки детек-торов УФ-излучения [9,10]. Среди пяти полиморфных фаз оксида галлия фаза β-Ga 2 O 3 является наиболее стабильной вплоть до температуры плавления 1800 • C [11].…”
Section: Introductionunclassified